Śrī Annamācāryulu, Yakṣagāna saṃpradāyaṃ - Abbūri, Gōpālakṛṣṇa (Abbūri Ṭrasṭ, 2002)
On kirtanas of Tallapaka Annamacharya, 1408-1503, Telugu poet; focus on tradition of Yakṣagāna plays.
Includes bibliographical references (p. [351]-354) - In Telugu
Keywords: Telugu-Sprache; Tāḷḷapāka Annamācārya; Poetik; Yakshagana